If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -22 = 2x + 34 Reorder the terms: -22 + 6x = 2x + 34 Reorder the terms: -22 + 6x = 34 + 2x Solving -22 + 6x = 34 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -22 + 6x + -2x = 34 + 2x + -2x Combine like terms: 6x + -2x = 4x -22 + 4x = 34 + 2x + -2x Combine like terms: 2x + -2x = 0 -22 + 4x = 34 + 0 -22 + 4x = 34 Add '22' to each side of the equation. -22 + 22 + 4x = 34 + 22 Combine like terms: -22 + 22 = 0 0 + 4x = 34 + 22 4x = 34 + 22 Combine like terms: 34 + 22 = 56 4x = 56 Divide each side by '4'. x = 14 Simplifying x = 14
| 0.7(3x+3)=1.1-(x+2) | | 4(8-5x)=2x-4 | | 2/3x-5/6=10 | | X/3-4=-6 | | (t-10)(t+11)= | | p=s/14 | | x^3-20x^2+64x=0 | | 8/9z-1/2=-2/3z+1/6 | | 300+2x-125-7x=75 | | 1/3(1/2-1/3)-1/3(1/3-1/2) | | u-v=18 | | 3/5x+5=14 | | 2n^2-2n=7 | | 3-(x+1)=2-(x+6) | | w-6=8 | | 3(-4x-4)-5=16 | | 2(n-6)-(9+3n)=-2n | | 6+8(4w+3)= | | v/15=u | | x/y=1/2 | | 3c+c=24 | | 3x+18=23-2x | | -15+-13= | | 10-(2y-2)=1-3y | | 10=m+n | | 0.4x+3=0.7x-3 | | 10x=42-4x | | y-18=x | | 9x=22-2x | | 3(x+2)=13 | | 4/3=12/x-3 | | 12=b/a |